IMPLEMENTASI PROGRAM TPM (TOTAL PRODUCTIVE MAINTENANCE) MESIN CJ4 DI PT. KIMBERLY-CLARK INDONESIA - IGR Arya Wiguna (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract. The objective this research is to review the effectiveness of CJ4machine by the program of Total Productive Maintenance (TPM) in PT KimberlyClark Indonesia. The research is descriptive method (case study) by usingquantitative and qualitative approach. The measurement of effectivess level CJ4machine of PT KCI using method Overall Equipment Evectivenss (OEE), whichits calculation starting on January-December 2014 found that the value is still lowcompared with the standard value < 85% (world class manufacture-JIPMstandard). The dominant factor that cause losses at CJ4 machine were: breakdownloss and reduced speed loss. The suggestion for the future are: do thecomprehensive traing for the operator for increasing their skills and conductinginspection material holisticly, did not randomly either before entering thewarehouse nor before the matherial is being used and applied 5S program, andalso always doing continuous improvement (Kaizen). This value should beimproved to achieve the world class manufacture according to Japan InstitutePlant Maintenance.Keywords: Total productive maintenance, Overall equipment effectiveness, 5S,Autonomous maintenance, Preventive maintenance.